Pemberian Daun Kayu Manis Cinnamomun Burmanni dalam Pakan Terhadap Kinerja Pertumbuhan dan Komposisi Nutrien Tubuh Ikan Patin Pangasius Hypopthalmus - Mia Setiawati; Dedi Jusadi; Shella Marlinda; Dadang Syafruddin (Institut Pertanian Bogor, 2014)
This research was carried out to evaluate the effect of cinnamon leaf (Cinnamomun burmanni) as a suplement inthe diet due to growth performance and nutriet composition of patin (Pangasius hypothalamus). A triplicateexperiment was conducted using fish with an initial body weight of 7.27 ± 0.28 g. Fish were culture in aquaria 50 x40 x 35 cm at a density of 10 fish/aquaria. Fish were fed on the diet contained either 0, 0.5, 1; or 1.5% respectively.Fish fed on the diet at satiation for 30 days. The result shows that the suplementation of cinnamon leaf powder inthe diet 0 to 1.5% was insignificantly affected feed consumption, specific growth rate, and survival rate of fish.However, the addition of Cinnamomumn burmanni up to 1% was significantly increased the level of total feeddigestibility twice, the protein digestibility to 87.39%, and protein retention 1.5 higher than the control (withoutcinnamon leaf powder). On the other hand, the diet of 1% Cinnamomumn burmanni were the optimal result of thisresearch with the feed efficient, decrease 30% of fat and have more compact flesh texture.